A Critical Analysis of Orientalist’s on Economic Resources of Holy Prophet (ﷺ) - Dr. Farhat Aziz (Seerat Studies, 2023)
This research paper deals with the criticism of Western scholars on economic resources of Holy Prophet (ﷺ) in the light of Islamic inheritance. Orientalist’s have refused to acknowledge the Prophet Muhammad (ﷺ) as the last Prophet of Allah Almighty. They are trying their horizontal best to reject the Islamic faith i.e. Qur’an. Muhammad as a prophet. They have assisted all their efforts to prove for this purpose that Qur’an is not the book of Allah and consequently the Prophet Muhammad (ﷺ) as a fictitious Prophet. The purpose of this research paper is to provide authentic information on the economic resources of the Holy Prophet (ﷺ) and his family, In this paper, the debate about the provision of the Orientalists criticism on economic resources is divided under a few subtitles so that the whole picture emerges. Some of the orientalists believe that the economic condition of the Prophet (ﷺ) was severe and weak from the beginning, He (ﷺ) had lived his life in compassion and depends on others, After marrying Hazrat Khadija, her wealth improved His (ﷺ) economic life and the livelihood. Another economic resource of the Messenger of Allah was only booty. However, some other orientalists believe that Prophet of Allah belongs from a rich family but He ﷺ) had sacrificed his wealth for the mission of Allah. These sorts of point of view by orientalists have been analyzed in this research by consulting the non - Muslim authors’ books and the basic sources of Islamic Inheritance.